2011
DOI: 10.1007/s00586-011-1707-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of transversus abdominis muscle contraction ratio during abdominal hollowing: a useful tool to distinguish between patients with chronic low back pain and healthy controls?

Abstract: Spine stabilisation exercises, in which patients are taught to preferentially activate the transversus abdominus (TrA) during ''abdominal hollowing'' (AH), are a popular treatment for chronic low back pain (cLBP). The present study investigated whether performance during AH differed between cLBP patients and controls to an extent that would render it useful diagnostic tool. 50 patients with cLBP (46.3 ± 12.5 years) and 50 healthy controls (43.6 ± 12.7 years) participated in this case-control study. They perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 42 publications
9
65
0
1
Order By: Relevance
“…21,37,49,56 As USI is noninvasive, relatively inexpensive, and portable, its use has become more widespread to assess the morphology (form and size) of muscle 57,58 and connective tissues. 31 As muscles and connective tissues remodel in response to loading, their morphological characteristics can provide insight into their loading history.…”
Section: T T Resultsmentioning
confidence: 99%
“…21,37,49,56 As USI is noninvasive, relatively inexpensive, and portable, its use has become more widespread to assess the morphology (form and size) of muscle 57,58 and connective tissues. 31 As muscles and connective tissues remodel in response to loading, their morphological characteristics can provide insight into their loading history.…”
Section: T T Resultsmentioning
confidence: 99%
“…24,32 Selecting a TrA activation cutoff for the ability to contract the TrA effectively during the ADIM was difficult, due to the variance in reported values. 4,27,36,44,54,66,67 One study reported that LBP patients could achieve a TrA activation of above 2.0 with minimal training. 66 Others have found TrA activations of healthy individuals to be around 1.4.…”
Section: Discussionmentioning
confidence: 99%
“…22 These investigators found agreement between EMG amplitude and ultrasound data but did not complete a formal analysis. 22 Regardless, ultrasound imaging has been utilized in a number of studies investigating abdominal muscle thickness change as an indicator of muscle activation between groups of individuals with lumbar spine pathology, 2,4,15,27,28,30,44,54,59,66 healthy individuals, 4,6,7,31,36,44,54,64,67 and as an intervention outcome. 25,28,31,59 Activation of the TrA may be quantified by examining the ratio of muscle thickness during contraction to muscle thickness at rest, which is known as the TrA activation ratio (TrA contracted thickness/TrA relaxed thickness).…”
Section: T T Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[32][33][34] Q ualSyst scores ranged from 0.19 to 1. Most studies were found to have m oderate to high quality, 11,13,[32][33][34][35][36][37][38][39][40][41][42][43][44] with only 5 studies scoring below 0.75 31,[45][46][47][48] (Table 1 ). Results of the Q AREL ranged from three to seven (Table 2 ).…”
Section: Risk O F Bias Wit Hin St Udiesmentioning
confidence: 99%